Porcine lungs perfused with three different flows using the 8-h open-atrium cellular ex vivo lung perfusion technique - Buttar, Sana N.; Møller-Sørensen, Hasse; Perch, Michael; Kissow, Hannelouise; Lilleør, Thomas N. B.; Petersen, Rene H.; Møller, Christian H. (Frontiers in Bioengineering and Biotechnology, 2024)
Number of lung transplantations is limited due to the shortage of donor lungs fulfilling the standard criteria. Ex vivo lung perfusion (EVLP) technique provides the ability of re-evaluating and potentially improving and treating marginal donor lungs. Accordingly, the technique has emerged as an essential tool to increase the much-needed donor lung pool. One of the major EVLP protocols, LUND protocol, characterised by high pulmonary artery flow (100% of cardiac output (CO)), an open atrium and a cellular perfusate, has demonstrated encouraging short EVLP duration results. However, potential of the longer EVLP duration of the protocol is yet to be investigated – a duration which is seen necessary to rescue more marginal donor lungs in future. This study aimed to achieve stable 8-hours EVLP using open atrium, cellular model with three different pulmonary artery flows in addition to determine the most optimal flow in terms of best lung performance including lung electrolytes and least lung edema formation, perfusate and tissue inflammation and histopathological changes using porcine model. EVLP was performed using flow of either 40%- (n=6), 80%- (n=6) or 100% (n=6) of CO. No flow rate demonstrated stable 8-hours EVLP. Stable 2-hours EVLP was seen in all three groups. Insignificant deterioration was observed in Dynamic compliance, Peak airway pressure and Oxygenation between the groups. Pulmonary vascular resistance increased significantly in 40% group (p < .05). Electrolytes demonstrated an insignificant worsening trend with longer EVLP. Interleukin-8 (IL-8), in perfusate and tissue, wet-to-dry weight ratio and histopathological changes after EVLP were insignificantly time-dependent between the groups. This study demonstrated that stable 8-hours EVLP was not feasible in an open atrium cellular model regardless of flow of 40%-, 80%-, or 100% of CO. No flow was superior in terms of lung performance, lung electrolytes changes, least lung edema formation, minimal IL-8 expression in perfusate and tissue and histopathological changes.